2007
DOI: 10.1103/physrevlett.98.258701
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Size Scaling in Complex Networks

Abstract: A finite-size-scaling (FSS) theory is proposed for various models in complex networks. In particular, we focus on the FSS exponent, which plays a crucial role in analyzing numerical data for finite-size systems. Based on the droplet-excitation (hyperscaling) argument, we conjecture the values of the FSS exponents for the Ising model, the susceptible-infected-susceptible model, and the contact process, all of which are confirmed reasonably well in numerical simulations.PACS numbers: 05.50.+q, 89.75.Hc, 89.75.Da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(164 citation statements)
references
References 34 publications
(46 reference statements)
9
154
1
Order By: Relevance
“…Such a claim was criticized by Park and collaborators [11], who later proposed an alternative FSS ansatz, based on a droplet excitation theory [12]. A discrimination between the two approaches turned out to be nontrivial: Even for simulations on annealed networks, which are expected to be described exactly by mean-field theory, numerical results did not satisfactorily conform to any of the two competing theories [13].…”
Section: Introductionmentioning
confidence: 94%
“…Such a claim was criticized by Park and collaborators [11], who later proposed an alternative FSS ansatz, based on a droplet excitation theory [12]. A discrimination between the two approaches turned out to be nontrivial: Even for simulations on annealed networks, which are expected to be described exactly by mean-field theory, numerical results did not satisfactorily conform to any of the two competing theories [13].…”
Section: Introductionmentioning
confidence: 94%
“…For spatially embedded random networks, it has been shown that a useful definition of d, different from the embedding space dimension, can be given [50], and a connection to classical percolation scaling theory can be drawn based on this definition. A different case is that of the nonspatial complex networks, where it has been proposed that the product νd can be replaced byν in the case that the criticality belongs to the mean-field universality class [51]. In our scaling analysis below we will therefore consider only the combined expressions γ /νd and 1/νd.…”
Section: Finite-size Scaling Methodsmentioning
confidence: 99%
“…The usual QS analysis assumes a power law dependence of the order parameters with the size at criticality. Such assumption is commonly used as a criterion to determine the critical point of absorbing phase transitions in regular lattices [11] and has been extended to quenched complex networks [19,20]. Corrections to scaling in the form 1 − const × N −0.75 were already observed in QS simulations of the directed percolation universality class in hypercubic lattices, including the contact process [24,32].…”
Section: B Scaling At Criticalitymentioning
confidence: 99%